Character analysis of Erin Gruwell from Freedom Writers - Sarair, Sarair; Apriliani, Apriliani; Farsia, Lina (Accentia: Journal of English Language and Education, 2023)
This study analyzed Erin Gruwell, a character from the movie Freedom Writers. The goals of this study were to explore Erin Gruwells personality, examine her salient traits, and learn interesting information about her. This study used a descriptive method and employed qualitative research. Data were examined by viewing the movie scenes and comprehending the movie script. The characters of Erin could be categorized into one of eight groups depending on their personalities and roles: protagonist, antagonist, underdog, sidekick, round, flat, static, and dynamic. In terms of roles and personalities, Erin Gruwell, the protagonist, had two different types of characters: protagonist and round. There were three distinct categories of characteristics: psychotism, extraversion, and neuroticism. The findings revealed that extraversion was the key quality of Erin Gruwell. In addition, Erin Gruwell also had intriguing behaviors, attitudes, and habits based on her personality and role.